A Semiotic Analysis of Educational Symbols and School Identity in Selected Public Secondary Schools in Oyo East Local Government Area, Oyo State, Nigeria - Aimasiko, Omobolaji Ganiyu; Enu, Eveln Nwene (NIU Journal of Educational Research; Vol 12 No 2 (2026): NIU Journal of Educational Research, Vol. 12, No. 2, June 2026DO - 10.58709/niujed.v12i2.2578, 2026)
Signs and symbols are fundamental to human communication. They are regarded as the means through which meaning is constructed, negotiated and transmitted. Educational symbolic elements contribute to the creation of school identity. The issue of identity construction in schools have gained relevance in recent research; but there is still limited gap given to semiotic functions in meaning making as it relates to educational symbols. This study carries out a semiotic analysis of educational symbols in selected public secondary schools in Oyo East Local Government Area of Oyo State. The study is anchored on the integration of Social Semiotics Theory by Kress and Van Leeuwen and Peircean Semiotic theory by Charles Sanderson Peirce.  This integration is adopted to ensure an in-depth framework for the analysis of the educational symbols in a bid to provide analytical precision. The study adopted a qualitative research design. The population of the study is made up of all secondary schools in Oyo East Local Government Area. Three schools were selected through purposive sampling. Data for the study were gotten from the visual and textual elements namely school logos and uniform colours. The findings of the study reveals that the logo and uniform of the selected schools function as complementary semiotic resources in the construction of institutional identity. Drawing on Peircean Semiotics, the visual elements of the logo—such as the shield, crossed tools, circular frame, and textual inscriptions operate predominantly as symbols, relying on shared cultural values. From a Social Semiotics perspective, the meaning potential of these elements is realised through multimodality, where visual, linguistic, and colour modes interact to produce a unified message. The symbols help in the construction of institutional identity among the educational edifices. The study concludes that school visual identities are not merely decorative, but are loaded with ideological depth and create a system of communication that actively shape how institutions are perceived and understood within their social contexts. Keywords:   Semiotics, Educational Symbols, Identity Construction.